Psychiatric Emergency Hospitalization-Meanings, Feelings, Perceptions and the Family Expectation. - Bellini, Luana Cristina; Paiano, Marcelle; Ciccone Giacon, Bianca Cristina; Silva Marcon, Sonia (Revista de Pesquisa: Cuidado é Fundamental)
Objective: The study's purpose has been to grasp the family members' perceptions regarding the psychiatric hospitalization of one of their members. Methods: It is a descriptive-exploratory study with a qualitative approach. The study's participants were eight relatives of individuals hospitalized in the Psychiatric Emergency Service of a General Hospital. The data were collected in July 2017, through semi-structured interviews, which were transcribed in full and submitted to the thematic analysis process using the IRAMUTEQ® software. Results: The following three thematic axes were identified: The family meanings concerning the mental disorders; The psychiatric emergency hospitalization from the family's viewpoint; The perceptions about medication and therapeutic resources. Conclusion: Some families have greater difficulty in accepting the psychiatric hospitalization of one of their members than others. The feelings generated and the routine change, they all differ between the families that have a mental disorder bearing person and those who have chemical dependents with an associated basal disorder.